MR Imaging of Peripheral Nerves Using Targeted Application of Contrast Agents: An Experimental Proof-of-Concept Study - Tereshenko, Vlad; Pashkunova-Martic, Irena; Manzano-Szalai, Krisztina; Friske, Joachim; Bergmeister, Konstantin D.; Festin, Christopher; Aman, Martin; Hruby, Laura A.; Klepetko, Johanna; Theiner, Sarah; Klose, Matthias H. M.; Keppler, Bernhard; et al. (Frontiers in Medicine, 2020)
Introduction: Current imaging modalities for peripheral nerves display the nerve’s structure but not its function. Based on a nerve’s capacity for axonal transport, it may be visualized by targeted application of a contrast agent and assessing the distribution through radiological imaging, thus revealing a nerve’s continuity. This concept has not been explored, however, may potentially guide the treatment of peripheral nerve injuries. In this experimental proof-of-concept study, we tested imaging through MRI after administering gadolinium-based contrast agents which were then retrogradely transported. Methods: We synthesized MRI contrast agents consisting of paramagnetic agents and various axonal transport facilitators (HSA-DTPA-Gd, chitosan-DTPA-Gd or PLA/HSA-DTPA-Gd). First, we measured their relaxivity values in vitro to assess their radiological suitability. Subsequently, the sciatic nerve of 24 rats was cut and labeled with one of the contrast agents to achieve retrograde distribution along the nerve. One week after surgery, the spinal cords and sciatic nerves were harvested to visualize the distribution of the respective contrast agent using 7T MRI. In vivo MRI measurements were performed using 9.4 T MRI on the 1st, 3rd and the 7th day after surgery. Following radiological imaging, the concentration of gadolinium in the harvested samples was analyzed using inductively coupled mass spectrometry (ICP-MS). Results: All contrast agents demonstrated high relaxivity values, varying between 12.1 and 116.8 mM−1s−1. HSA-DTPA-Gd and PLA/HSA-DTPA-Gd application resulted in signal enhancement in the vertebral canal and in the sciatic nerve in ex vivo MRI. In vivo measurements revealed significant signal enhancement in the sciatic nerve on the 3rd and 7th day after HSA-DTPA-Gd and chitosan-DTPA-Gd (p < 0.05) application. Chemical evaluation showed high gadolinium concentration in the sciatic nerve for HSA-DTPA-Gd (5.218±0.860 ng/mg) and chitosan-DTPA-Gd (4.291±1.290 ng/mg). Discussion: In this study a novel imaging approach for the evaluation of a peripheral nerve’s integrity was implemented. The findings provide radiological and chemical evidence of successful contrast agent uptake along the sciatic nerve and its distribution within the spinal canal in rats. This novel concept may assist in the diagnostic process of peripheral nerve injuries in the future.